ANALISIS PERBEDAAN KINERJA DAN PENGARUH DIVERSIFIKASI USAHA TERHADAP KINERJA PERUSAHAAN MANUFAKTUR - Lim, Meilya; Lindrawati, Lindrawati; Dwijayanti, S, Patricia Febrina (Widya Mandala Surabaya Catholic University, 2014)
Business diversification is an expantion that purpose to create value by adding one or more business units. The firms that focus on a single segment often compares with divercification firms to determine the performance of each other. Therefore, this research has purposes to exemine the difference of performance between single firm and diversified firm, to exemine the impact of business diversification to performance of firm, and to exemine the difference of performance between firms that develop through related diversification and firms that develop through unrelated diversification. The object of the research are 43 manufacturing firms that listed in the Indonesian Stock Exchange in the year of 2008 to 2012, using the purposive sampling technic and the research data are panel pooled data. From 43 firms, 7 firms are firms that focus on a single segment , and 36 firms are diversified firm. The hypotheses’ examinations are using the independent samples test and the double linear regression. The results of the research showed that there were significant performance difference between the performance of single firms and the performance of diversified firms, and regression analysis showed that diversification hasn’t a significant impact on performance. Beside that, the result of the research also showed that there weren’t significant performance difference between the performance of firms that develop through related diversification and the performance of firms that develop through unrelated diversification.